Impacts of subsidized credit on the optimum level of post-crisis investment of Brazilian firms - Patrick Franco Alves; Ludmilla Lorrany Mattos Silva; Rafael Lima de Morais (Institute for Applied Economic Research (ipea), 2018)
Firms' investment decisions involve analyzing prices, products, technologies, productive capacity and the availability of credit. These and other factors were greatly impacted by the 2009 post-crisis economic environment in Brazil. We measure the after crisis impacts of subsidized credit on the optimal level of investment of Brazilian firms from the perspective of the Tobin's q. We combined the Tobin's q framework with the estimation of a panel data stochastic frontier model to establish what optimal levels of investment the subsidized firms should have had. In general the after crisis average-q was very low and it appeared to differ substantially across subsidized and non-subsidized firms. The result indicates a relative disequilibrium between the value of the company and its assets in the post-crisis Brazilian environment. Firms with access to subsidized credits from Brazilian Development Bank (BNDES) did not have higher optimal investment levels, indicating that the crowding out effect can be happening.
Keywords: D25; G28; H24; H54; G18; 330